Pertanggung Jawaban Pidana Debt Collector dalam Melakukan Penarikan Kendraan Bermotor Secara Paksa Terhadap Konsumen - Rahmawati Rahmawati; Roy Marthen Moonti; Nurwita Ismail; Muslim A. Kasim (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This research examines the criminal liability of debt collectors involved in forcibly seizing motorized vehicles from consumers. Such actions, often conducted by third parties representing finance companies, frequently occur without proper legal procedures and involve violence, coercion, or violations of consumer rights. The study responds to ongoing incidents where debt collectors act with force, while legal enforcement remains insufficient. Utilizing an empirical normative legal approach, the study combines a review of relevant laws—such as the Criminal Code (KUHP), Consumer Protection Law, and Financial Services Authority regulations with field research, including interviews with victims and observations in Kayubulan Village, Limboto Subdistrict, Gorontalo Regency. The findings reveal that debt collectors who repossess vehicles without official documentation, prior notification, or through intimidation may be committing criminal acts under Article 368 of the KUHP (extortion) and Article 335 (unpleasant acts). These actions clearly conflict with legal norms and consumer protection principles. The study recommends that finance institutions strengthen oversight of third-party collectors and ensure all collection activities comply with legal and ethical standards. Additionally, raising public legal awareness is essential, particularly regarding consumer rights and available legal remedies against coercion or unlawful conduct during debt collection. This dual strategy enhancing institutional accountability and empowering consumers aims to bridge the gap between law and practice, ensuring justice and legal protection in financial transactions.